Evaluation of the Implementation of the Creative Economy Program in Makassar through Analysis of Regulatory Documents and White Papers - Achmad Amzal Maulana; Ampauleng; Salma Abdullah; Siti Fatimah (LPPM STIEM BONGAYA, 2026)
This study aims to evaluate the implementation of creative economy programs in Makassar City through a systematic review of local government regulations and official reports. The background of this study rests on the strategic role of the creative economy as a driver of innovation-based, cultural, and technology-oriented economic growth, as emphasized in national policy documents such as the Medium-Term National Development Plan (RPJMN) and the directives of the Creative Economy Agency (Bekraf) prior to its integration into the Ministry of Tourism and Creative Economy. At the local level, the Makassar City Government has demonstrated its commitment through several regulations and programs implemented by related agencies such as the Department of Tourism and the Department of Cooperatives and SMEs. This research employs a qualitative approach with content analysis of policy documents, including regional regulations, the 2021–2026 Regional Development Plan (RPJMD), strategic plans (Renstra) of local agencies, performance accountability reports (LKjIP), and program budget realization reports from the last five years. The analysis focuses on policy objectives, alignment between planning and implementation, performance indicators, budget realization, and implementation challenges. The results indicate that, although a supportive regulatory and policy framework exists, the implementation of creative economy programs in Makassar remains suboptimal. Key obstacles include weak cross-sector coordination, limited budget allocation for creative subsectors, the absence of a comprehensive mapping of all 17 creative economy subsectors, and inadequate performance indicators to measure real impacts. Moreover, limited involvement of local creative actors in policy formulation and evaluation constrains policy effectiveness